Dynamic Characteristic Improvement of Phase-Shift Full-Bridge Center-Tapped Converters Using a Model Predictive Control - Bak, Yeongsu; Lee, Young Jae; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2022)
This article proposes a dynamic characteristic improvement of phase-shift full-bridge center-tapped (PSFB-CT) converter using a model predictive control (MPC) method. The PSFB-CT converter is widely used for low-voltage dc-dc converters in electric vehicles. In general, its output voltage is a control object which is usually controlled using a proportional-integral control-based output voltage controller and current controller. However, it has a disadvantage such as undesirable dynamic characteristic of the PSFB-CT converter and the necessity of gain tuning. Especially, if the gain of the PI control is increased to improve the dynamic characteristic of the PSFB-CT converter, an overshoot of the output voltage can occur. In this article, the advanced voltage control using the MPC method is proposed to improve the dynamic characteristic of the PSFB-CT converter without overshoot of the output voltage. As a result, the proposed method has advantages with not only fast dynamic characteristic but also robustness from a sudden change of load impedance. The effectiveness of the proposed MPC method was proved by the simulation and experimental results.
Keywords: Inductor; Low voltage DC-DC converters; Low voltage DC/DC converter; Model predictive control method; Model-predictive control; Optimal controls; Phase shift full bridges; Phase-shift full-bridge center-tapped converter; Predictive control; Predictive control methods; Rectifier; Vehicle's dynamics; Low-voltage dc-dc converter (LDC); model predictive control (MPC) method; phase-shift full-bridge center-tapped (PSFB-CT) converter